Potential of Shredded Ramie Fibers as Reinforcement in Recycled Polypropylene Composites: Analysis of Tensile and Bending Strength - Rebia, Rina Afiani; Sabila, Faroh; Primananda, Ade (Indonesian Journal of Chemical Research, 2025)
In the development of composite technology, synthetic fiber reinforcers are gradually being replaced by natural fibers. This shift is driven by growing awareness of environmental issues and the scarcity of petroleum resources, prompting researchers to explore the potential of natural fibers. This study used scraped ramie fiber (SRK) as a reinforcer, with recycled polypropylene (PP) serving as the matrix. The mixture ratios used between PP/SRK (%) were as follows: 90/10, 80/20, 70/30, 60/40, and 50/50. Before use, the scraped ramie fiber (SRK) was subjected to pretreatment with 5% NaOH to improve the mechanical bonding. The hot press technique was used to fabricate the PP/SRK composite. The physical and mechanical properties of the PP/SRK composite were analyzed through weight, thickness, volume, density, tensile strength, and bending strength measurements. The results of physical measurements obtained density values ​​for all samples between 0.73 - 0.76. The tensile test results showed a maximum stress value of 9.91 MPa and a strain value of 7.60% at the PP/SRK ratio 50/50. Then, the maximum modulus of rupture (MOR) was 23.49 MPa, and the modulus of elasticity (MOE) was 1.78 GPa at the PP/SRK ratio of 50/50.